2014
DOI: 10.1158/1055-9965.epi-14-0311
|View full text |Cite
|
Sign up to set email alerts
|

Smoking at Diagnosis Is an Independent Prognostic Factor for Cancer-Specific Survival in Head and Neck Cancer: Findings from a Large, Population-Based Study

Abstract: Background: Some studies suggest smoking may result in poorer clinical outcomes in head and neck cancer, but the evidence is heterogeneous and some of it is poor quality. In a large, population-based, study we investigated: (i) whether smoking at diagnosis is an independent prognostic factor for cancer-specific survival in head and neck cancer; and (ii) whether the association varies by site and treatment.Methods: Head and neck cancers (ICD10 C01-C14, and C30-32) diagnosed from 1994 to 2009 were abstracted fro… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

9
70
7
13

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(99 citation statements)
references
References 75 publications
9
70
7
13
Order By: Relevance
“…In our sample, unmarried patients were more likely to be current smokers. This is important, as smoking is known to negatively impact HNC survival by reducing treatment effectiveness (Browman et al, ; Sharp, McDevitt, Carsin, Brown, & Comber, ). A greater percentage of unmarried patients were current drinkers in our study, but this did not reach statistical significance.…”
Section: Discussionmentioning
confidence: 99%
“…In our sample, unmarried patients were more likely to be current smokers. This is important, as smoking is known to negatively impact HNC survival by reducing treatment effectiveness (Browman et al, ; Sharp, McDevitt, Carsin, Brown, & Comber, ). A greater percentage of unmarried patients were current drinkers in our study, but this did not reach statistical significance.…”
Section: Discussionmentioning
confidence: 99%
“…De acuerdo con la bibliografía publicada, el consumo de tabaco en pacientes portadores de cáncer de cabeza y cuello disminuye la sobrevida como consecuencia de la mayor incidencia de comorbilidades, principalmente cardiovasculares y respiratorias, así como la presencia de nuevos tumores primarios (23) . El uso de tabaco se asocia al aumento de complicaciones posoperatorias hasta seis veces más (24) , a lo que se le agrega la mortalidad por patología cardiovascular y respiratoria (25,26) . Nuestros resultados podrían atribuirse al bajo núme-ro de no tabaquistas en nuestra población y al alto porcentaje de alcoholistas en este grupo.…”
Section: Discussionunclassified
“…One study reported that the effect of smoking was evident only among the chemoradiotherapy or radiotherapy group [37]; another, found that smoking status was the strongest predictor of survival, in both current and former smokers [38]; a third large population-based study from Ireland, involving 5652 patients with HNC, reported significantly increased cancer-related death rate for current smokers with oral cavity, pharyngeal, and laryngeal cancers, and the association was stronger in surgically treated patients [39]. Moreover, the association between cigarette smoking and survival has been demonstrated also in colon [40], pancreatic cancer [41], renal cell carcinoma [42], oropharyngeal [43], and nasopharyngeal carcinoma [44] highlighting a possible enduring effects of smoking, even after stopping.…”
Section: Discussionmentioning
confidence: 99%